2011
DOI: 10.1029/2011ja017063
|View full text |Cite
|
Sign up to set email alerts
|

The response of the coupled magnetosphere-ionosphere-thermosphere system to a 25% reduction in the dipole moment of the Earth's magnetic field

Abstract: [1] The Earth's magnetic field changes in orientation and strength over time. We study the response of the magnetosphere-ionosphere-thermosphere system to a 25% reduction in magnetic field intensity, using the coupled magnetosphere-ionosphere-thermosphere (CMIT) model. Simulations were performed with a dipole moment of 8 × 10 22 A m 2 , close to the present-day value, and a dipole moment of 6 × 10 22 A m 2 , both under the same solar wind conditions, intermediate solar activity (F10.7 = 150), and for March equ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
89
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 41 publications
(99 citation statements)
references
References 28 publications
7
89
3
Order By: Relevance
“…near the northern hemisphere (NH) and southern hemisphere (SH) magnetic poles, with a cooling of up to 10 K in the NH and a warming of up to 12 K in the SH. In other areas a more modest warming is found of about 4 K. The overall warming is consistent with the overall decrease in magnetic field strength that has taken place over the past century (Cnossen et al 2011, while the more localized changes near the magnetic poles are probably associated with the northward and westward movement of the magnetic poles over the past century, which creates changes in the distribution and amount of Joule heating in the auroral regions Fig. 1.…”
Section: Neutral Temperaturesupporting
confidence: 60%
See 1 more Smart Citation
“…near the northern hemisphere (NH) and southern hemisphere (SH) magnetic poles, with a cooling of up to 10 K in the NH and a warming of up to 12 K in the SH. In other areas a more modest warming is found of about 4 K. The overall warming is consistent with the overall decrease in magnetic field strength that has taken place over the past century (Cnossen et al 2011, while the more localized changes near the magnetic poles are probably associated with the northward and westward movement of the magnetic poles over the past century, which creates changes in the distribution and amount of Joule heating in the auroral regions Fig. 1.…”
Section: Neutral Temperaturesupporting
confidence: 60%
“…The underlying physical mechanisms responsible for these effects were explored through a series of idealized modeling studies and are now quite well understood (Cnossen et al 2011). Yet, the importance of geomagnetic field changes as a driver of long-term change in the upper atmosphere still appears to be underappreciated.…”
Section: Introductionmentioning
confidence: 99%
“…[13] The simulations with both models were set up in the same way as described by Cnossen et al [2011]. The Earth's magnetic field was approximated by a centered dipole, with the NH geomagnetic pole at 80 N, 70 W. Each simulation started at 00:00 UT on 21 March (equinox) or 21 June (solstice), and was run for 36 h. We used a moderate solar activity level (F10.7 = 150) and idealized solar wind conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Clilverd et al (2002) concluded from a simple calculation that involved various assumptions and approximations that changes in the Earth's magnetic field would have little effect on geomagnetic activity. However, a detailed analysis has not been done yet, and the simulations by Cnossen et al (2011) indicate that the effect may be larger than previously thought, due to a stronger dependence of the ionospheric conductance on the magnetic field strength than was assumed by Clilverd et al (2002). When considering the effects of changes in geomagnetic activity on the upper atmosphere, it is therefore possible that these may ultimately be due to changes in the Sun and/or changes in the Earth's magnetic field.…”
Section: Geomagnetic Activitymentioning
confidence: 79%
“…With this model it is now possible to include the effects of changes in high-latitude magnetosphere-ionosphere coupling, and Cnossen et al (2011) have started to use this to re-assess the effects of changes in the magnetic field on the ionosphere and thermosphere.…”
Section: Effect Estimates and Comparison To Observationsmentioning
confidence: 99%